2007
DOI: 10.1016/j.jmb.2006.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of the HIV-1 Gag Protein in Solution

Abstract: A single multi-domain viral protein, termed Gag, is sufficient for assembly of retrovirus-like particles in mammalian cells. We have purified the human immunodeficiency virus type 1 (HIV-1) Gag protein (lacking myristate at its N terminus and the p6 domain at its C terminus) from bacteria. This protein is capable of assembly into virus-like particles in a defined in vitro system. We have reported that it is in monomer-dimer equilibrium in solution, and have described a mutant Gag protein that remains monomeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
146
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(163 citation statements)
references
References 50 publications
17
146
0
Order By: Relevance
“…These results are in agreement with chemical cross-linking studies that showed that Gag is predominantly dimeric in the cytoplasm and does not form higher order oligomers until it reaches the plasma membrane (7). Gag trimerization in the presence of inositol phosphate derivatives has been reported previously (8). However, no evidence for the existence of a ΔGag trimer or higher order structures (e.g., hexamer comprising a trimer of dimers) was found by analytical ultracentrifugation either in the presence of inositol hexakisphosphate (K dimer = 35 ± 5 ÎŒM) or nucleic acids (K dimer = 14-18 ÎŒM) (Table S1 and Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in agreement with chemical cross-linking studies that showed that Gag is predominantly dimeric in the cytoplasm and does not form higher order oligomers until it reaches the plasma membrane (7). Gag trimerization in the presence of inositol phosphate derivatives has been reported previously (8). However, no evidence for the existence of a ΔGag trimer or higher order structures (e.g., hexamer comprising a trimer of dimers) was found by analytical ultracentrifugation either in the presence of inositol hexakisphosphate (K dimer = 35 ± 5 ÎŒM) or nucleic acids (K dimer = 14-18 ÎŒM) (Table S1 and Fig.…”
Section: Resultssupporting
confidence: 92%
“…A previous hydrodynamic and neutron scattering study of a monomeric variant of Gag, obtained by a double mutation (W316A and M317A) at the dimerization interface, claimed that MA and NC are close to one another in three-dimensional space (8). The current RDC data, however, are inconsistent with this proposal because the values of D NH a and η for MA and the two zinc knuckles of NC are very different from one another (Table S2).…”
Section: Significancementioning
confidence: 67%
“…These spheres are not as uniform and are significantly larger than the particles reported for the wild-type p6-deleted Gag constructs (5,27,29). Intriguingly, the size distribution of the particles formed by the ⌬177 Gag in vitro is similar to the one observed in vivo for a Gag mutant with impaired CA-CTD dimerization (31). Moreover, the size of the virus-like particles formed by the p6-deleted Gag was shown to be influenced by inositol phosphates (32), and the C-terminal domain of the CA seems to be involved in the inositol phosphate binding (33).…”
Section: Resultsmentioning
confidence: 69%
“…The recombinant HIV-1 Gag protein was prepared as described (Datta et al 2007) and solubilized in a buffer containing 20 mM Tris HCl pH 7.4, 0.5 M NaCl, 5 mM DTT, 1 mM PMSF, and a protease inhibitors cocktail (Roche Inc.). These conditions are taken in consideration for translation experiments performed in the presence of this protein to maintain equivalent levels of salt, pH, DTT, and antiprotease in each reaction tube.…”
Section: Protease Antibodies Recombinant Gag Protein and Other Reamentioning
confidence: 99%